Design of a morphing airfoil - Tan, Hao Chong (2014)
This report studies the aerodynamic effects of a small single shape-morphing hump on a 2D NACA 4412 airfoil surface under a free stream of 0.7 Mach number and various cruising angle of attacks ranging from 0 degree to 4 degrees. The results are collected using Reynolds Averaged Navier Stokes Simulations (RANS) solver from well known Computational Fluid Dynamics (CFD) software known as ANSYS Fluent.